CDNF protects the nigrostriatal dopamine system and promotes recovery after MPTP treatment in mice - Airavaara, Mikko (2011)
Cerebral dopamine neurotrophic factor (CDNF) is a recently discovered protein, which belongs to the evolutionarily conserved CDNF/MANF family of neurotrophic factors. CDNF has been shown to promote the survival of midbrain dopamine neurons in vivo. The degeneration of dopamine neurons following 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) -treatment is well characterized and efficacy in this model is considered a standard criterion for development of parkinsonian therapies. MPTP is a neurotoxin, which produces parkinsonian symptoms in humans, and in C57/Bl6 mice. To date, there are no reports about the effects of CDNF on dopamine neuron survival or function in the MPTP rodent model, a critical gap. Therefore, we studied whether CDNF has neuroprotective and neurorestorative properties for the nigrostriatal dopamine system after MPTP injections in C57/Bl6 mice. We found that bilateral striatal CDNF injections, given 20-h before MPTP, improved horizontal and vertical motor behavior. CDNF pre-treatment increased tyrosine hydroxylase (TH)-immunoreactivity in the striatum and in the substantia nigra pars reticulata (SNpr), as well as the number of TH-positive cells in substantia nigra pars compacta (SNpc). Post-treatment with CDNF, given 1 week after MPTP injections, increased horizontal and vertical behavior of mice, as well as dopamine fiber densities in the striatum and the number of TH-positive cells in SNpc. CDNF did not alter any of the analyzed dopaminergic biomarkers or locomotor behavior in MPTP-untreated animals. We conclude that striatal CDNF administration is both neuroprotective and neurorestorative for the TH-positive cells in the nigrostriatal dopamine system in the MPTP model, which supports the development of CDNF-based treatment for Parkinson’s disease.